ZAKAT SEBAGAI PENGURANG PENGHASILAN KENA PAJAK BAGI WAJIB PAJAK DI KOTA BANJARMASIN - Zhaputri, Tsuroyya Nurtyas; Ainun, Basyirah; Handayani, Lusiana (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
The purpose of this paper is to investigate how the ta x payers in Banjarmasin City applied Law No. 23 Article 22 and 23  Year 2011 about zakat as a deduction of Tax Income. The method of this research is descriptive qualitative with analytical technique is descriptive analysis. Moslem who is eligible for zakat obligation and as tax payers occurred double liability, paid for tax and zakat obligation simultaneously all this time. The government has solved this double liability problem by released a law No. 36 Year 2008 about Tax Income. Government Regulation No. 60 Year 2010 about zakat or compulsory religious contributions and also an Act No. PER-33/PJ/2011 issued by Directorate General of Taxation, stated zakat obligation can be deducted from gross income. These statements then supported by The Law No. 23 Year 2011 about Zakat Management Article 22 stated that zakat paid by muzakki to BAZNAS or LAZ  will be deducted from gross income (1). Article 23 (1) stated that BAZNAS or LAZ were required to submit the proof of zakat deposit to muzakki and (2) the deposit proof meant in point (1) was used as a deduction to tax income. That proof was used as a deduction for gross income in the filling of Annual Tax Return. The study reveals that  most of the zakah payers also paid tax (56,90%). Almost 30% respondents has no idea zakat as a decution of tax income and 53.45% tend to paid zakat not through BAZ or LAZ because of their faith and belief. The rules of zakat which is stated in Law No. 23 Year 2011 Article 22 and 23 had still not been applied by the tax payers in Banjarmasin City because of its not well socialized.